Written corrective feedback at university: Detection of errors by teachers and impact of different forms of feedback - Birello, Marilisa; Comajoan-Colomé, Llorenç; Salguero, Tania; Sorolla, Natxo (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2025)
This study explores the written corrective feedback provided by two university teachers in the academic texts written by their students. Specifically, it focuses on the relationship established between the linguistic and discursive errors identified by the teachers, the forms of feedback provided (direct, indirect, metalinguistic and metadiscursive) and the impact of feedback on a second version of the texts revised by the students. A total of 142 texts (two versions of 71 texts) submitted by two groups of students taking a primary education degree at two Spanish universities (71 students) were analyzed. These were coded according to the errors detected, the form of feedback provided, and the way in which they incorporated the feedback into a second version. The results show that the errors detected in the highest numbers by the teachers were discursive, followed by morpho-syntactic and spelling mistakes. The most common feedback was indirect, followed by metalinguistic, although the two teachers were found to take distinct approaches. Regarding its impact, the students incorporated a high percentage (80%) of the feedback provided.